Spending on Research and the Returns to Education in Italy - Cipollone, Piero (2012)
The essay reviews the different notions of returns to education ordinarily used in the economic policy debate and provides estimates of the quantitative importance of each. Investment in education is profitable both for individuals and for society even from the strictly economic standpoint; and including the effects of education on other dimensions of individual and collective welfare only strengthens this conclusion. The various indicators also show that the returns to investment in education, especially for younger people, are lower in Italy, despite the country's severe shortage of human capital. This paradoxical situation raises serious problems for economic policy in Italy, because the price signals that the market is transmitting to agents do not favour the rapid accumulation of knowledge that is needed in order to escape from the slow-growth trap.